Microstructural, Mechanical, and Tribological Properties of Selective Laser Melted Inconel 718 Alloy: The Influences of Heat Treatment - Ümit Gencay Başcı; Egemen Avcu; Mertcan Kıraç; Ahmet Sever; İdris Gökalp; Hasan İsmail Yavuz; Serkan Oktay; Eray Abakay; Yasemin Yıldıran Avcu; Rıdvan Yamanoğlu (Crystals)
The present study investigates the microstructural, mechanical, and tribological properties of Inconel 718 alloy produced by selective laser melting (SLM) in relation to heat treatment. The SLM-processed samples received a two-step heat treatment: solutionizing at 1065 °C for 1 h, followed by double aging at 720 °C for 8 h and 620 °C for 6 h. The as-built sample exhibited a grain structure mostly characterized by fine Laves phases, while the hardening phases γ′ ((Ni3 (Al, Ti)) and γ″ (Ni3Nb) precipitated during the heat treatment. Following heat treatment, a transformation in crystallographic texture and dislocation density occurred, yielding a random texture and reduced dislocation density, particularly in the XZ direction, attributed to the formation of new grains via recrystallization in the microstructure. The grain size in the XY plane decreased following heat treatment, whereas the texture in the <001> direction remained unaffected. The heat-treated samples had significantly higher tensile strength (1330 MPa vs. 960 MPa) and hardness (530 HV vs. 340 HV) relative to the as-built samples. The wear resistance of heat-treated samples surpassed that of the as-built sample due to enhanced mechanical properties resulting from the fine and dispersed γ′ and γ″ precipitates in the microstructure with heat treatment.